2007
DOI: 10.1186/cc5704
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia increases ventilator-induced lung injury via mitogen-activated protein kinases: a prospective, controlled animal experiment

Abstract: Introduction Large-tidal volume (V T ) mechanical ventilation and hyperoxia used in patients with acute respiratory distress syndrome can damage pulmonary epithelial cells through lung inflammation and apoptotic cell death. Hyperoxia has been shown to increase ventilator-induced lung injury, but the mechanisms regulating interaction between large V T and hyperoxia are unclear. We hypothesized that the addition of hyperoxia to large-V T ventilation would increase neutrophil infiltration by upregulation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
104
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 30 publications
(56 reference statements)
7
104
0
Order By: Relevance
“…2), 28 and lung compliance, 28,32,33 increased inflammatory mediator expression ( Fig. 3) 24,[26][27][28]31,36 as well as increased apoptosis, 26,33,34 and increased alveolar infiltration by neutrophils. 24,26,27,[31][32][33]36 Similar results were found even when moderate hyperoxia (F IO 2 ϭ 0.5) was combined with a V T of 25 mL/kg.…”
Section: Impact Of Vili and Hyperoxic Acute Lung Injurymentioning
confidence: 93%
See 2 more Smart Citations
“…2), 28 and lung compliance, 28,32,33 increased inflammatory mediator expression ( Fig. 3) 24,[26][27][28]31,36 as well as increased apoptosis, 26,33,34 and increased alveolar infiltration by neutrophils. 24,26,27,[31][32][33]36 Similar results were found even when moderate hyperoxia (F IO 2 ϭ 0.5) was combined with a V T of 25 mL/kg.…”
Section: Impact Of Vili and Hyperoxic Acute Lung Injurymentioning
confidence: 93%
“…24,[26][27][28][29][30][31][32][33][34][35][36] These models mimic common clinical strategies in managing ARDS and other forms of acute respiratory failure before the advent of lung-protective ventilation. In brief, compared with controls, high-V T ventilation with ambient F IO 2 (0.21), or a physiologic V T with hyperoxia, the combination of high-V T (18 -30 mL/kg) ventilation, and hyperoxia (F IO 2 ϭ 0.8 -1.0) markedly enhanced numerous signifiers for VILI, including: altered-permeability pulmonary edema formation, 24,26,27,31,32 diffuse interstitial and alveolar hemorrhage, 33,34 decreased surfactant production (Fig. 2), 28 and lung compliance, 28,32,33 increased inflammatory mediator expression ( Fig.…”
Section: Impact Of Vili and Hyperoxic Acute Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperoxia has been shown to increase VILI, but the mechanisms regulating interaction between large tidal volume (VT) and hyperoxia are still unclear. Li et al [32] hypothesized that the addition of hyperoxia to large tidal volume ventilation would increase neutrophil infiltration by upregulation of the cytokine macrophage inflammatory protein-2 (MIP-2) and would increase apoptosis via the mitogen-activated protein kinase pathways. Authors concluded that hyperoxia increased high-VT-induced apoptotic and non-apoptotic epithelial cell injury and resulted in increased lung neutrophil influx.…”
Section: Positive End-expiratory Pressure (Peep)mentioning
confidence: 99%
“…Previously, in vitro studies demonstrated that mechanical stretch may activate apoptotic cell death (dos Santos et al, 2004;Edwards et al, 1999;Hammerschmidt et al, 2004). Moreover, several investigators reported enhanced apoptosis after 2 to 5 hours of mechanical ventilation with high tidal volumes (Chiang et al, 2011;Le et al, 2008;Li et al, 2007). Although the precise role of necrotic cell death has not been elucidated in VILI yet, it has been demonstrated in vitro that mechanical stretch as such induces necrosis (Hammerschmidt et al, 2004;Tschumperlin et al, 2000).…”
Section: Cell Deathmentioning
confidence: 99%